SI‐CLP inhibits the growth of mouse mammary adenocarcinoma by preventing recruitment of tumor‐associated macrophages - Yin, Shuiping; Wang, Nan; Riabov, Vladimir; Mossel, Dieuwertje M.; Larionova, Irina; Schledzewski, Kai; Trofimova, Olga; Sevastyanova, Tatyana; Zajakina, Anna; Schmuttermaier, Christina; Gratchev, Alexei; Flatley, Andrew; et al. (International journal of cancer, 2020)
What's new? Chitinase‐like proteins possess cytokine‐like properties and can manipulate cancer progression. Here the authors show that stabilin‐1 interacting chitinase‐like protein (SI‐CLP) inhibits ...
First published: 16 September 2019
Gesehen am 19.01.2021